Estudo do comportamento do centro de pressão no equilíbrio estático e dinâmico - Nora, Fernanda Grazielle da Silva Azevedo (2012)
Postural stability is an important ability of the human body in standing position as well as in dynamic activities like locomotion. It influences all motor and muscle aspects related to the execution of a motor task and is achieved by appropriate support conditions, coordinated muscle activity and proprioceptive information. The center of pressure behavior can be studied under different conditions, providing information on how the body reacts to postural instabilities. Thus the main purpose of this study is to propose a methodology for the study of the center of pressure behavior in order to evaluate static and dynamic equilibrium conditions of the human body. In order to achieve the goals, the structure of this thesis is composed of three studies. The equilibrium control during single leg ballet poses and the anticipatory postural adjustments prior to the first step in gait were discussed in the first and second study respectively. In the third study, methodological aspects were reviewed and a data processing standardization to study the center of pressure behavior during gait initiation was proposed. Dynamometry with force platforms was the measurement method used for all studies. The results allow to identify balance control strategies in ballet dancers and anticipatory postural adjustments existing during the transition from standing still to the cyclic gait steps. Some clinical applications of the results are presented and also directions for future studies.